Regulations on the Distribution of Skincare Products and Legal Certainty Regarding Consumer Safety and Security Rights - Tuti Haryanti; Rosdalina Bukido; Nasaruddin Umar (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyze the regulations governing the distribution of skincare products and the legal safeguards for consumer rights. The distribution of skincare products is becoming increasingly widespread and has the potential to harm consumers, particularly through marketing and sales on social media, which allow products to be discovered and purchased without adequate education. This study is a normative study using primary and secondary legal sources. The legal materials collected were analyzed by presenting existing theories logically and systematically to obtain significant and scientific results, followed by the formulation of recommendations. The results of the study indicate that the state has made efforts to ensure protection and legal certainty for consumers of skincare products through the establishment of regulations. However, existing regulations have not comprehensively addressed the distribution of skincare products, such as mechanisms for product transfer and the use of products without a doctor’s recommendation. This is due to the lack of clear boundaries between skincare and cosmetics within a legal framework. Additionally, current regulations still prioritize administrative obligations for business operators, thereby failing to ensure legal certainty and protection for consumers. Therefore, there is a need to redefine the concept of cosmetics in legislation and reformulate the regulations governing the distribution of skincare products. The existing legal provisions do not align with the legal ideal of providing benefits and legal certainty for consumers.